White lupin leads to increased maize yield through a soil fertility-independent mechanism: a new candidate for fighting Striga hermonthica infestation? - Weisskopf, Laure; Akello, Pollycarp; Milleret, Roxane; Khan, Zeyaur R.; Schulthess, Fritz; Gobat, Jean-Michel; Le Bayon, Renée-Claire (My University, 2009)
Nitrogen (N)-deficiency and lack of phosphorus (P) availability are major constraints to maize yields in Western Kenya. In a two-season field study in the lake Victoria basin, we tested the capacity of white lupin (Lupinus albus (L.), cv. Ultra), as a nitrogen-fixing crop with a highly efficient P-acquisition capacity, to increase maize yields when used as a companion or cover crop, or as a source of organic matter. Each experiment was performed on three different fields (Vertisols) differing in N/P availability, previous cropping history and in levels of infestation by the parasitic weed Striga hermonthica (Del.) Benth. Our results show that white lupin led to significantly higher yields of maize when used as a cover crop. When lupin was grown as a companion crop, it also slightly enhanced the yield of the co-cultivated maize. When lupin shoots were incorporated to the soil, the positive effect of lupin on maize growth was field-dependent and only occurred in the field most heavily infested with S. hermonthica. Despite the beneficial impact on maize yield, no clear effect of lupin on soil N and P availability or on maize N/P uptake were observed. In contrast, lupin significantly inhibited infestation of maize by S. hermonthica: when lupin was grown together with maize in pots inoculated with S. hermonthica, the emergence of the weed was strongly reduced compared to the pots with maize only. This work opens a new range of questions for further research on white lupin and its potential beneficial impact as a S. hermonthica-inhibiting crop.
Keywords: Lupinus albus; Desmodium uncinatum; Striga hermonthica; Zea mays; Soil fertility; Cluster roots